Inventory Information System Design Analysis (Case Study at CV. Mysneaker Retail Indo) - Zaki, Achmad; Kamila, Edita Rachma; Violita, Cynthia Eka (GREENOMIKA, 2023)
This research is a qualitative research that examines the design of inventory information systems at CV. Mysneaker Retail Indo. This study analyzes the information system on inventory at CV. Mysneaker Retail Indo. This study uses observation with interviews. The results of this observation are written on the observation sheet carried out by the observer. Unstructured interviews were conducted in order to obtain more comprehensive interview results with informants. Research data was collected through observation, unstructured interviews, and documentation. CV. Mysneaker Retail Indo has collaborated with a third service party, namely mokapos, to help carry out the inventory system for this business by the end of 2022. This application is available on desktop and mobile. This application makes inventory management in managing inventory fast and accurate so as to minimize errors in data. This business uses Use Case Diagrams. Use Case Inventory Diagram proposed, there are several involved in the system namely Warehouse Admin, Marketing and Owner.